2020
DOI: 10.3389/fimmu.2020.01424
|View full text |Cite
|
Sign up to set email alerts
|

Structural Understanding of Interleukin 6 Family Cytokine Signaling and Targeted Therapies: Focus on Interleukin 11

Abstract: Cytokines are small signaling proteins that have central roles in inflammation and cell survival. In the half-century since the discovery of the first cytokines, the interferons, over fifty cytokines have been identified. Amongst these is interleukin (IL)-6, the first and prototypical member of the IL-6 family of cytokines, nearly all of which utilize the common signaling receptor, gp130. In the last decade, there have been numerous advances in our understanding of the structural mechanisms of IL-6 family sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 342 publications
0
58
0
2
Order By: Relevance
“…nisms for complex formation, evidencing the biological specificity for each ligand-receptor pair [28]. Consistently across all family members, site II is always the binding site for the shared receptor gp130/IL6ST.…”
Section: Soluble Receptors and Signalling Modesmentioning
confidence: 73%
See 1 more Smart Citation
“…nisms for complex formation, evidencing the biological specificity for each ligand-receptor pair [28]. Consistently across all family members, site II is always the binding site for the shared receptor gp130/IL6ST.…”
Section: Soluble Receptors and Signalling Modesmentioning
confidence: 73%
“…A recent study has reported on the different mecha- Site I, used only by some cytokines, is a binding site for non-signalling receptors only (e.g., IL6R for IL6 or IL11R for IL11). A recent study has reported on the different mechanisms for complex formation, evidencing the biological specificity for each ligandreceptor pair [28]. Consistently across all family members, site II is always the binding site for the shared receptor gp130/IL6ST.…”
Section: The Il6-like Cytokine Familymentioning
confidence: 83%
“…Plasma IL-11 levels were negatively correlated with BAX protein production in liver biopsies. IL-11 is also soluble [ 22 , 28 ] and is blocked by sgp130 binding. How sgp130 affects the pathways triggered by these cytokines and how these pathways influence the effects of sgp130 deserve further study.…”
Section: Discussionmentioning
confidence: 99%
“…IL-11, a major member of the IL-6 proteins family, was involved in the production of ECM in normal physiological processes, such as embryonic development, reproduction, and tissue remodeling, as well as in disease processes. 26 F I G U R E 5 IL-11 promotes fibrosis expressions by up-regulating collagen I and collagen III in LF fibroblasts. A, The quantitative real-time PCR analysis showing mRNA levels of fibrosis-related genes (COL1A2 and COL3A1) in LF cells at 12 hours and 24 hours (n = 4).…”
Section: Discussionmentioning
confidence: 99%